Quantitative analysis and comparison of BMI among Han, Tibetan, and Uygur University students in northwest China - Jingya, Bai; Ye, He; Jing, Wang; Xi, Huanjiu; Tao, Hai (Hindawi Publishing Corporation, 2013)
Objectives. To fully analyze and compare BMI among Han, Tibetan, and Uygur university students, to discuss the differences in their physical properties and physical health, and thus to provide some theoretical suggestions for the improvement of students’ physical health. Methods. The cross-sectional random cluster sampling was used to investigate 10103 Han, Tibetan, and Uygur university students, aged 20–24 in Northwest China, and their height and weight were measured to calculate BMI. The BMI classification criteria for Chinese established by Work Group on Obesity in China (WGOC) were used for screening. Results. Han, Tibetan, and Uygur university students show low obesity rates but high overweight rates. Han, Tibetan, and Uygur university students present a high rate of underweight, normal weight, and overweight, respectively. Female Han students show higher underweight and normal weight rates, but lower overweight and obesity rates, than male Han students. Female Tibetan students show higher normal weight rate, but lower overweight and obesity rates, than male Tibetan students. BMI increases with age for male students but decreases with age for female students. Male Uygur students show higher obesity rate than female Uygur students. Tibetan and Uygur university students have higher BMI than other minorities in South China.